2001
DOI: 10.1037/0096-1523.27.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Location and frequency cues in auditory selective attention.

Abstract: The roles of frequency and location cues in auditory selective attention were investigated in a series of experiments in which target tones were distinguished from distractors by frequency, location, or the conjunction of frequency and location features. When frequency separations in high-rate tone sequences were greater than 1 octave, participants were fastest at identifying targets defined by frequency and were sometimes faster at identifying conjunction than location targets. Frequency salience diminished a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 61 publications
(90 reference statements)
3
47
2
Order By: Relevance
“…Although location was processed faster than pitch on average, irrelevant changes in pitch across consecutive trials still exerted a detrimental effect on RTs during location processing (see also Experiment 3 in Dyson & Quinlan, 2004). These kinds of observations support the idea of a special role for frequency within audition (see also Kubovy, 1981;Kubovy & Van Valkenburg, 2001;Purves et al, 1997;Woods, Alain, Diaz, Rhodes, & Ogawa, 2001), in that participants are seemingly unable to ignore the processing of frequency during acoustic stimulation. Consistent with this data, the ERPs from Experiment 3 provide support for this specific role, in the conditionindependent elongation of the processing period between P2 and P3 for cases of ƒ 0 repetition (see Figure 3).…”
Section: A Special Role For Frequency?supporting
confidence: 62%
“…Although location was processed faster than pitch on average, irrelevant changes in pitch across consecutive trials still exerted a detrimental effect on RTs during location processing (see also Experiment 3 in Dyson & Quinlan, 2004). These kinds of observations support the idea of a special role for frequency within audition (see also Kubovy, 1981;Kubovy & Van Valkenburg, 2001;Purves et al, 1997;Woods, Alain, Diaz, Rhodes, & Ogawa, 2001), in that participants are seemingly unable to ignore the processing of frequency during acoustic stimulation. Consistent with this data, the ERPs from Experiment 3 provide support for this specific role, in the conditionindependent elongation of the processing period between P2 and P3 for cases of ƒ 0 repetition (see Figure 3).…”
Section: A Special Role For Frequency?supporting
confidence: 62%
“…Although the observation of a conjunction cost in audition is a relatively novel finding, a similar cost has also recently been described by Woods, Alain, Diaz, Rhodes, and Ogawa (2001). Here, a variant of the simple go/no-go task was reported in which only two locations (i.e., left and right) and two frequencies (i.e., 1500 and 250 Hz) were used.…”
Section: Other Related Workmentioning
confidence: 88%
“…In order to accommodate the observation of both conjunction costs and benefits, Woods et al (2001) argued that a conjunction benefit is most likely to arise when at least one of the constituent features (typically, the location value) takes a relatively long amount of time to be recovered. In contrast, when both features are recovered quickly, a conjunction cost will arise.…”
Section: Other Related Workmentioning
confidence: 99%
“…However, spatial cues affected a pitch discrimination task only when the cue was informative, suggesting a more conscious or endogenous mechanism. This suggests that frequency may be automatically encoded during any auditory attention task, whereas the encoding of auditory spatial information is dependent on the specifics of the experimental procedure (see also Buchtel & Butter, 1988;Mondor & Zatorre, 1995;Rhodes, 1987;Woods, Alain, Diaz, Rhodes, & Ogawa, 2001). To date, this hypothesis has not received unequivocal support, however; Mondor, Zatorre, & Terrio (1998, Experiment 2) found that even when performing a task on an orthogonal dimension, both frequency and location cues influenced performance, even when they were uninformative.…”
Section: Relevance To the Theory Of Indispensable Attributes (Tia)mentioning
confidence: 99%